2020
DOI: 10.1016/j.oneear.2020.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Six Decades of Glacier Mass Changes around Mt. Everest Are Revealed by Historical and Contemporary Images

Abstract: Highlights d Glaciers around Mt. Everest have thinned by more than 100 m since the 1960s d The rate of ice mass loss has consistently accelerated over the past six decades d Glacier thinning has occurred at above 6,000 masl d Surge-type glacier behavior has been identified for the first time in the region

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 64 publications
(102 reference statements)
2
52
0
Order By: Relevance
“…a −1 between 1984 and 2001, and -0.44 ± 0.12 m w.e. a −1 between 2001 and 2018 (King, Bhattacharya, et al, 2020) in agreement with geodetic values from other studies of −0.27 ± 0.08 m w.e. a −1 between 1970 and 2007 (Bolch et al, 2011) and −0.45 ± 0.52 m w.e.…”
Section: Glacier Morphometrysupporting
confidence: 91%
See 1 more Smart Citation
“…a −1 between 1984 and 2001, and -0.44 ± 0.12 m w.e. a −1 between 2001 and 2018 (King, Bhattacharya, et al, 2020) in agreement with geodetic values from other studies of −0.27 ± 0.08 m w.e. a −1 between 1970 and 2007 (Bolch et al, 2011) and −0.45 ± 0.52 m w.e.…”
Section: Glacier Morphometrysupporting
confidence: 91%
“…a −1 during 2000–2016 compared to 1975–2000 in response to climate change (Maurer et al., 2019). The acceleration in mass loss is expressed by the rate of surface elevation change, which has increased dramatically at Khumbu Glacier since 1969 (King, Bhattacharya, et al., 2020). Glacier mass loss is occurring due to atmospheric warming and is regionally variable, due to topographic feedbacks between climate systems and ice flow (Dehecq et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Another study also found consistent acceleration of glacier mass loss around Mt. Everest region between the 1960s (−0.23 ± 0.12 m w.e.a −1 ) and the modern era (−0.38 ± 0.11 m w.e.a −1 from 2009 to 2018) 58 .…”
Section: Resultsmentioning
confidence: 64%
“…In the Himalayas, the two reporting reference glaciers had negative balances averaging −487 mm. King et al (2019) identified that in the Mount Everest region mass loss has increased each of the last 6 decades. In 2020, the post-monsoon season and early winter were warm and dry in the Himalayas, leading to the ablation season extending into January with the snow line retreating over 100 m from October into January (Fig.…”
Section: ) Alpine Glaciers-m Peltomentioning
confidence: 99%